Molecular structure of (m5 dC-dG)3: the role of the methyl group on 5-methyl cytosine in stabilizing Z-DNA. - Fujii, S (1982)
The hexamer (m5 dC-dG)3 has been synthesized and its three-dimensional structure determined by a single crystal X-ray diffraction analysis. The structure has been refined to a final R value of 15.6% at 1.3 A resolution. The molecule forms a left-handed Z-DNA helix which is similar to the unmethylated Z-DNA structure. The presence of the methyl group has resulted in slight changes in the twist angle between successive base pairs and modification of some of the interatomic contacts. Methylation of cytosine in the C5 position is associated with a relative destabilization of the B-DNA structure and a stabilization through hydrophobic bonding of the Z-DNA structure.